Comparing the inter-seed effect for some iodine-125 brachytherapy sources through a Monte Carlo simulation approach. (September 2022) - Baghani, Hamid Reza; Gheibi, Azar; Mowlavi, Ali Asghar
Highlights: Inter-seed effect (ISE) was evaluated for some commercial I-125 brachytherapy seeds. 6711, ProstaSeed, STM 1251, 3500, and IAI-125A seed models were considered. Minimum and maximum ISE were respectively found for prostaseed and 3500 seeds. ISE can affect the dose distribution around multiseed brachytherapy implants. Abstract: Background and Objective: One of the principal deficits of TG-43(U1) dosimetry protocol is ignoring the attenuation effect of each seed during the multiseed brachytherapy implants. To take into account this shadowing effect, a parameter known as the inter-seed effect ( ISE ) has been introduced. Current study aims to evaluate and compare the ISE for some I-125 brachytherapy seeds through a Monte Carlo (MC) simulation approach. Methods: Five different models of I-125 seeds including 6711, ProstaSeed, STM 1251, 3500, and IAI-125A were simulated by MCNPX MC Code. Validity of simulated seed models was confirmed through comparing the corresponding dosimetric parameters such as radial dose function and anisotropy function with those reported by relevant literature. Then, the ISE for each seed at different distances was determined in three seeds implant configuration. Additionally, the relevant attenuation factors ( AF ) were also determined for each brachytherapy source. Results: The obtained results demonstrated that minimum inter-seed attenuation belongs to the ProstaSeed. In return, the maximum inter-seed attenuation was found for 3500 brachytherapy seed. The mean attenuation factor for 6711, ProstaSeed, STM 1251, 3500, and IAI-125A seed models was equal to 0.764, 0.829, 0.785, 0.594, and 0.772, respectively. Conclusions: It can be concluded that the considered I-125 brachytherapy seeds show different inter-seed effects and mean AF values for the same multiseed implant arrangement. This finding can be attributed to discrepancies in internal seed design and configuration.